Overexpression of a ceramide synthase gene,GhCS1, inhibits fiber cell initiation and elongation by promoting the synthesis of ceramides containing dihydroxy LCB and VLCFA - Li, Guiming; Wang, Qiaoling; Meng, Qian; Wang, Guanhua; Xu, Fan; Chen, Qian; Liu, Fang; Hu, Yulin; Luo, Ming (Frontiers in Plant Science, 2022)
Cotton is an important natural fiber crop worldwide. Cotton fiber cell is regarded as an ideal material for studying the growth and development of plant cells. Sphingolipids are important components of biomembrane and bioactive molecules which participate in many processes such as plant growth, development regulation, stimulus sensing, and stress response. However, the functions of sphingolipids in the cotton fiber development are still unclear. In the present study, we identified a cotton ceramide synthase gene, GhCS1, which is predominantly expressed in fiber cell. The GhCS1 is located in the endoplasmic reticulum and has the conserved domains of ceramide synthase. Overexpression of GhCS1 gene inhibited both vegetative and reproductive growth in cotton. Importantly, the fiber cell initiation and elongation were severely inhibited when compared with control. Comparison of the sphingolipid profile in the 0-DPA (days past anthesis) ovule (with fiber cell) between control and transgenic cotton plants showed that the content of sphingosines (Sph) decreased significantly in transgenic ovules, whereas the content of phyto-sphingosines (Phyto-Sph) had no change. Meanwhile, the content of ceramide containing Sph and very-long-chain fatty acid (VLCFA) increased significantly in transgenic ovules, while ceramide containing Phyto-Sph and long-chain fatty acids (LCFA)/VLCFA significantly decreased. These results indicated that GhCS1 was a functional ceramide synthase, which preferentially used Sph and VLCFA as substrates and was different from the Arabidopsis ceramide synthase AtLOH1/AtLOH3, which preferentially used Phyto-Sph and VLCFA as substrates, and also different from AtLOH2, which preferentially used Sph and LCFA as substrates. It is suggested that GhCS1 might be a new ceramide synthase gene in the plant, play some roles in the development of fiber cells and cotton plants.